Penerapan Metode Teorema Bayes Dalam Mendiagnosa Penyakit Tubercolosis - Nyipto Wibowo, Gentur Wahyu; Widiastuti, Sri; Muratno, Muratno; Lolang, Enos; Soraya, Soraya (Building of Informatics, Technology and Science (BITS), 2023)
In human life, health is the most valuable asset. a healthy body and soul gives happiness to everyone. But sometimes circumstances make human health decline. One of the causes of declining human health is due to viruses or bacteria that spread without people knowing it. One of the infectious diseases is tuberculosis (TB). Tuberculosis is a disease that occurs due to an infection caused by a bacterium called Mycobacterium tuberculosis. TB is a disease that spreads very easily, namely by air. The patient will spread germs through the air if the patient coughs or sneezes. Death is not uncommon because those with symptoms are afraid to go to the hospital for medical check-ups because they are hampered by a lack of funds. This situation is very concerning. Because of these circumstances, technological developments can be used as an alternative solution in replacing or assisting in diagnosing diseases experienced by people based on their symptoms. One of the technologies that develop about diagnosing disease is by using an expert system. An expert system is a system created by experts by developing technology based on science. In expert systems, their use must be combined with a method so that they can work properly and optimally. In this study the method used is the Bayes Theorem method. The Bayes Theorem method was developed by a priest named Thomas Bayes. The pastor comes from England who is a Presbyterian pastor. The Rev. Thomas Bayes developed Bayes' Theorem in 1763 and was perfected and redeveloped by an expert named Laplace. Based on the results of the above process, information was obtained that 87% of patients who consulted had pulmonary tuberculosis